La gobernanza transnacional de la migración ecuatoriana a través del codesarrollo - Cortés Maisonave, Almudena (Oñati Socio-Legal Series, 2011)
The purpose of this paper is to show the relationship between co-development projects with transnational interests and the governance of migration by the Spanish and Ecuadorian governments. On one hand, the emergence of co-development is linked with the political dimension of migration, and therefore, with the challenges that its management poses for both the sending and receiving states. Simultaneously, the state exists in a context of the reconfiguration of its traditional functions, and above all, the manner in which it goes about performing them. For these reasons, co-development projects form part of state governance strategies, based on a special understanding of the nexus between migration and development in European social space, involving international organizations, state governments, and civil society, linked by migratory flows. This is demonstrated in the case of Ecuador and Spain. Since Spain stimulated co-development, the implementation of projects with Ecuador has been emphasized, due to the dimensions achieved by Ecuadorian migration. Co-development politics and projects are analyzed in this paper as areas of intervention integrated by values, guide lines and cultural understandings about migration, including appropriate forms of control and management.